Strawberry, Washington County - Whetstone, Sara (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author uses newspaper articles and historic documents to tell the story of the town of Strawberry, Kansas. She is able to give an explanation of the towns growth and reasons for its eventual demise.
Sara Whetstone, “Strawberry, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/81.
Keywords: Strawberry; Washington County; Strawberry Dance Pavilion; Parson's Creek; John Gieber; Clifton